The Effects of Plant Leaves Variants from The Philippines on Infective Oesophagustonum dentatum Larvae - G. Beltran, Maria Asuncion; Robertson, Allan; J. Martin, Richard (Veterinary Biomedical and Clinical Journal, 2019)
Nine aqueous extracts of plant leaves from the Philippines were evaluated against Oesaphagustomum dentatum sensitive (ODSEns) larvae for their anthelmintic effects. The plant species evaluated were Ananas comosus, Chrysophyllum cainito,Gliricidia sepium, Annona squamosa, Moringa oleifera, Tinospora rumphii Boerl,Azadirachta indica, Trichantera gigantea and Leuacaena leucocephala. The leaves of the plants gathered from Camiling, Tarlac, Philippines, were dried under room temperature for 30 days and then ground. Aqueous extracts of these plant leaves were prepared using migration buffer. In vitro migration and inhibition assays were used to evaluate the anthelmintic activity against exsheathed third stage larvae of Oesophagustomum dentatum. The experiments were put in 24-well plates at room temperature with four replications per treatment using different concentrations of 1, 2.5, 5 and 10 mg/ml. About 120 larvae per well were deposited on a larval migration apparatus consisting of 20 Î¼m nylon mesh filters and incubated 20 hours under different treatments and another 2 hours to allow the migration of active motile larvae. The evaluation criteria were based on the average numbers of inhibited larvae under the different treatments. The percentage inhibition were statistically analyzed using Two-Way ANOVA (P=â‰¤.0001) of the Graph Pad Prizm software (V5 San Diego, Ca). The most effective leaves with their highest inhibition level were from Ananas comosus (pineapple, 86.50%), Gliricidia sepium (madre de cacao, 84.50%), Chrysophyllum cainito (star apple, 83.75%), Moringa oleifera (horseradish,58.75%), Annona squamosa (sweet sop, 56.00%), Tinospora rumphii Boerl ( \Makabuhay, 55.75%), and Azadirachta indica (Neem, 51.50%), whereby extremely significant (PË‚0.001) effect against O. dentatum larvae. Two leaves extracts, from Trichantera gigantea and Leuacaena leucocephala have no significant effect on O. dentatum larvae. The larval migration assay allows initial studies on the anthelmintic effects of the herbs.